Effect of Lamotrigine on fetal rat brain morphology - San, N; Pandit, RK; Dhungel, S (Janaki Medical College Journal of Medical Science, 2013)
Background and Objectives: Lamotrigine is a “second generation” anti-epileptic drug (AED) approved by the Food and Drug Administration (FDA) and is the first FDA-approved therapy after Lithium for maintenance treatment of bipolar I disorder. It crosses the placenta easily indicating that the maternal treatment leads to a considerable fetal exposure. This study is planned to study the morphological and histological changes induced by Lamotrigine in the fetal rat brain. Material and Methods: The morphological effect of lamotrigine on fetal rat brain was studied after giving four times its recommended therapeutic dose to 12 pregnant rats and placebo to 6 control rats during the period of organogenesis. The rats were sacrificed on the twentieth day of pregnancy. Body weight, body length, brain weight, brain volume, histological examination of the cerebral cortex and ventricular size of all the delivered fetuses were studied. Non-parametric Mann-Whitney test was used to compare the data. Results: There was no significant difference in mean body weight, mean body length, mean brain weight and mean brain volume in control and experimental rat fetuses. However one lamotrigine exposed rat fetus had exencephalic malformation and its histological study of the cerebral cortex revealed ill defined plexiform layer and dilated lateral ventricle. Conclusion: Probability that lamotrigine produces congenital malformation in fetal rats, when used during pregnancy, is low. DOI: http://dx.doi.org/10.3126/jmcjms.v1i1.7883 Janaki Medical College Journal of Medical Sciences (2013) Vol. 1 (1):26-29